2007
DOI: 10.1111/j.1468-3083.2007.02228.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity as an aetiological factor in vitiligo

Abstract: Vitiligo is a common dermatological disorder characterized by the presence on the skin of depigmented macules resulting from the destruction of cutaneous melanocytes. Autoimmunity is an important hypothesis with regard to vitiligo aetiology and the evidence for autoimmune responses being involved in the pathogenesis of this disorder will be discussed in the present review. All immune system compartments, including innate and adaptive immunity have been implicated in vitiligo development. Particularly relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
105
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 141 publications
(238 reference statements)
1
105
0
11
Order By: Relevance
“…18 High frequency of thyroid dysfunctions have been reported among vitiligo patients than in the normal controls. [18][19][20][21] In this study, 26.7% of the vitiligo patients were observed to have various degrees of thyroid dysfunctions which is in accord with the finding by Jishna et al, who reported an incidence rate of 27% of thyroid dysfunctions among vitiligo patients but at variance with the findings of Altraide et al in a retrospective study reported from Nigeria in 2009. 22,4 Altraide et al had reported a 9.8% frequency of thyroid dysfunctions among vitiligo subjects in their study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 High frequency of thyroid dysfunctions have been reported among vitiligo patients than in the normal controls. [18][19][20][21] In this study, 26.7% of the vitiligo patients were observed to have various degrees of thyroid dysfunctions which is in accord with the finding by Jishna et al, who reported an incidence rate of 27% of thyroid dysfunctions among vitiligo patients but at variance with the findings of Altraide et al in a retrospective study reported from Nigeria in 2009. 22,4 Altraide et al had reported a 9.8% frequency of thyroid dysfunctions among vitiligo subjects in their study.…”
Section: Discussionmentioning
confidence: 99%
“…5 This is evidenced by its familial propensities, histological proof of cytotoxic inflammatory cells in vitiligo lesions, its response to immunosuppressive agents and its frequent association with various autoantibodies and coexistence with other autoimmune disorders. [18][19][20][21] The theory of autoimmunity in etio-pathogenesis of vitiligo proposes alteration in both humoral and cellular immunity leading to the destruction of melanocytes and simultaneous involvement of various other organ-specific tissues. 18 High frequency of thyroid dysfunctions have been reported among vitiligo patients than in the normal controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Su etiología es aún incierta, sin embargo, ha sido establecido que en pacientes genéticamente susceptibles, factores como la autoinmunidad, las infecciones, el estrés, anormalidades neurológicas, disfunciones en el receptor de la melatonina, de la migración del melanocito y de origen tóxico, entre otros, podrían tener un rol patogénico 2 .…”
unclassified
“…(Ongenae et al, 2003;Engin et al, 2008). Anticorpos anti tirosinases, TRP 1 e 2, Pmell7, MelanA, MART-1,MCR-1, HLA-DR, fatores de transcrição SOX 9 e 10 ,interleucinas I e II, e super expressão dos receptores de superfície Fc e C3b nas células de Langerhans, assim como Imunoglobulinas IgG1, IgG2 e IgG3, e a proteína C3 da ativação do sistema complemento são ocasionalmente encontradas na membrana basal dos queratinócitos e melanócitos de pacientes com vitiligo (Rezaei et al, 2007).…”
Section: Introductionunclassified